State estimation for a dynamical system described by a linear equation with unknown parameters - Zhuk, S. M. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We investigate the state estimation problem for a dynamical system described by a linear operator equation with unknown parameters in a Hilbert space. In the case of quadratic restrictions on the unknown parameters, we propose formulas for a priori mean-square minimax estimators and a posteriori linear minimax estimators. A criterion for the finiteness of the minimax error is formulated. As an example, the main results are applied to a system of linear algebraic-differential equations with constant coefficients.